2021
DOI: 10.3390/socsci10120460
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Place Content: How Repetitive, Offensive, and Opinion-Challenging Social Media Posts Shape Users’ Unfriending Strategies in Spain

Abstract: Filtering strategies enable social media users to remove undesired content from their feeds, potentially creating homophilic environments. Although previous studies have addressed the individual-level factors and content features that influence these decisions, few have solely focused on users’ perceptions. Accordingly, this study applies social exchange theory to understand how users socially construct the process of unfriending. Based on 30 in-depth interviews with young Spaniards, we identify a widespread p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…As a legion of studies demonstrated, despite the changes in repertoires and consumption habits, media remain a primary source of knowledge about public affairs and politics, especially for short-term and contextual information (Castro et al, 2021; Jordá et al, 2021; Van Aelst et al, 2017). This positive association between media exposure and political knowledge appears firmer for legacy media and professional online outlets (Castro et al, 2021).…”
Section: Political Knowledge and Role Performance Of Public Mediamentioning
confidence: 99%
“…As a legion of studies demonstrated, despite the changes in repertoires and consumption habits, media remain a primary source of knowledge about public affairs and politics, especially for short-term and contextual information (Castro et al, 2021; Jordá et al, 2021; Van Aelst et al, 2017). This positive association between media exposure and political knowledge appears firmer for legacy media and professional online outlets (Castro et al, 2021).…”
Section: Political Knowledge and Role Performance Of Public Mediamentioning
confidence: 99%
“…Existing research shows that disagreements that violate fundamental moral values, are deemed disrespectful and uncivil, or are perceived to spread falsehood are culpable (Baysha, 2020;Goyanes & Skoric, 2021;Jordá, Cañedo, Bene, & Goyanes, 2021;Neubaum, Cargnino, Winter, et al, 2021;Schwarz & Shani, 2016). In-depth interviews often find participants describing someone they unfriended or a comment that triggered unfriending as "crossing the line"-going beyond what is considered to be the limits of acceptable discourse, such as offensive derogatory terms, hate speech, and comments that stir conflicts with close ones (Baysha, 2020;John & Gal, 2018;Jordá et al, 2021;Schwarz & Shani, 2016). This is accelerated in times of emotionally charged political conflicts as each side considers "some forms of expressions as offensive and unacceptable sacrilege and some words as taboos" (Schwarz & Shani, 2016, p. 393).…”
Section: Political Unfriending As Selective Avoidance In the Public S...mentioning
confidence: 99%
“…While research often evaluates the democratic implications of social media according to the normative theory of the public sphere, accounts of users' lived experiences consistently suggest that these digital spaces are perceived to be deeply personal, domestic, or at least semiprivate. Participants of in-depth interviews often described social media as an extension of their homes, such as "my home," "my neighborhood," "my wall," and "my world" (Bozdag, 2020;John & Gal, 2018;Jordá et al, 2021;Schwarz & Shani, 2016). Thus, these digital spaces are associated with a strong sense of ownership.…”
Section: Political Unfriending As Self-care In Personal Spacesmentioning
confidence: 99%
See 2 more Smart Citations